Early benefits of empagliflozin in patients with or without heart failure: findings from EMPA‐REG OUTCOME. (11th September 2020) - Pellicori, Pierpaolo; Ofstad, Anne Pernille; Fitchett, David; Zeller, Cordula; Wanner, Christoph; George, Jyothis; Zinman, Bernard; Brueckmann, Martina; Lindenfeld, JoAnn
Abstract: Aims: The EMPA‐REG OUTCOME trial demonstrated reductions in cardiovascular (CV) death and heart failure (HF) outcomes with empagliflozin, a sodium–glucose co‐transporter 2 inhibitor, in patients with type 2 diabetes and established CV disease over a study period of 3 years. We aimed to investigate the early benefit–risk profile of empagliflozin in patients enrolled in the EMPA‐REG OUTCOME trial according to HF status at baseline. Methods and results: The effects of treatments on glycated haemoglobin, systolic blood pressure and body weight, and on the HF endpoints of hospitalization for HF (HHF), HHF or CV death, and HHF or all‐cause mortality were evaluated at 12 weeks, 6 months, and 1 year after randomization. Occurrence of adverse events (AEs) during these time points was also evaluated. Compared with placebo, empagliflozin lowered glycated haemoglobin, systolic blood pressure, and body weight and rates of all the HF endpoints, as early as at 12 weeks, regardless of HF status at baseline. Favourable clinical and metabolic effects were maintained over time. AEs were generally higher in those with HF than without HF; however, compared with placebo, empagliflozin did not increase risk of developing AEs over the first year of treatment. Conclusions: In the EMPA‐REG OUTCOME trial, the use of empagliflozin led to early and beneficial effects on clinical, metabolic, and HF outcomes in patients with type 2 diabetes with or without HF at baseline, which were already apparent within 12 weeks from initiation of treatment. Over the first year of treatment, no safety concern was detected with the use of empagliflozin.